Gemingde youyi (Yazhou, Feizhou, Lading Meizhou pengyoumen canguan Zhongguo renmin geming junshi bowuguan) - Shen Jialin,
'Revolutionary friendship (Asian, African and South American friends visit the Chinese People's Revolutionary Military Museum).' Printno. 8085.2589.